2001
DOI: 10.1046/j.1365-294x.2001.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricuskollari: a tale of two lifecycles

Abstract: The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris, while in Iberia and North Africa the sexual generation host is cork oak, Q. suber. Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cerris from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
71
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 69 publications
9
71
1
1
Order By: Relevance
“…In some European species, the alternation of hosts from different series of oaks has been reported at each reproductive stage, which indicates that the specificity may not be exclusively limited to a particular host species (Askew 1984, Stone et al 2001. The specificity of gall-forming wasps has been poorly reviewed in the literature , and in Mexico, this group of insects and their ecological interactions have been poorly studied.…”
mentioning
confidence: 99%
“…In some European species, the alternation of hosts from different series of oaks has been reported at each reproductive stage, which indicates that the specificity may not be exclusively limited to a particular host species (Askew 1984, Stone et al 2001. The specificity of gall-forming wasps has been poorly reviewed in the literature , and in Mexico, this group of insects and their ecological interactions have been poorly studied.…”
mentioning
confidence: 99%
“…In this case, this problem can be solved by using RNA analysis. Th e intention of our study is not to carry out a RNA analysis but we are aware that there are authors working with RNA analysis at the species level of such taxa with parthenogenetic generations, as Stone et al (2001) and Rokas et al (2003) do with Cynipidae (the sister group to Figitidae).…”
Section: Discussionmentioning
confidence: 99%
“…The results of some important studies on gall wasps have indicated that Anatolia has been the main speciation center of the gall wasps in the past (Stone et al, 2001;Rokas et al, 2003). In order to make a precise estimation of the communities associated with Diplolepis galls in the western Palearctic, it is necessary to perform a comprehensive investigation of the community composition in Anatolia.…”
Section: Introductionmentioning
confidence: 99%